Monitoring the Perturbation of Soil and Groundwater Microbial Communities Due to Pig Production Activities - Hong, Pei-Ying (American Society for Microbiology, 2013)
This study aimed to determine if biotic contaminants originating from pig production farms are disseminated into soil and groundwater microbial communities. A spatial and temporal sampling of soil and groundwater in proximity to pig production farms was conducted, and quantitative PCR (Q-PCR) was utilized to determine the abundances of tetracycline resistance genes (i.e., tetQ and tetZ) and integrase genes (i.e., intI1 and intI2). We observed that the abundances of tetZ, tetQ, intI1, and intI2 in the soils increased at least 6-fold after manure application, and their abundances remained elevated above the background for up to 16 months. Q-PCR further determined total abundances of up to 5.88 × 10(9) copies/ng DNA for tetZ, tetQ, intI1, and intI2 in some of the groundwater wells that were situated next to the manure lagoon and in the facility well used to supply water for one of the farms. We further utilized 16S rRNA-based pyrosequencing to assess the microbial communities, and our comparative analyses suggest that most of the soil samples collected before and after manure application did not change significantly, sharing a high Bray-Curtis similarity of 78.5%. In contrast, an increase in Bacteroidetes and sulfur-oxidizing bacterial populations was observed in the groundwaters collected from lagoon-associated groundwater wells. Genera associated with opportunistic human and animal pathogens, such as Acinetobacter, Arcobacter, Yersinia, and Coxiella, were detected in some of the manure-treated soils and affected groundwater wells. Feces-associated bacteria such as Streptococcus, Erysipelothrix, and Bacteroides were detected in the manure, soil, and groundwater ecosystems, suggesting a perturbation of the soil and groundwater environments by invader species from pig production activities.